Spatial dynamics of chestnut blight disease at the plot level using the Ripley’s K function - Azevedo, João (2010)
We used the Ripley’s K function to describe the spatial dynamics of chestnut blight (Cryphonectria parasitica (Murrill) Barr) in sweet chestnut orchards to look at pattern in the pathogen distribution over time and the effect of the location of infected trees on the pattern of disease spread. We used data on infected and dead trees in 2003, 2004, 2005, and 2009 in 4 orchards located in Curopos parish, Portugal. We found both random and aggregated patterns of infected trees in the beginning of the study period and significant association of infected trees between successive dates, particularly at short distances. Two of the 4 studied orchards showed significant clustering of infected and dead trees in any of the dates observed but random spatial pattern in the remaining two which can possibly be explained by both natural propagation of the disease and management practices.